Usapang Tapat: Tungo sa Isang Katutubong Etika - Barbaza, Remmon E (Archīum Ateneo, 2020)
Dr. Barbaza discusses ethics and language, using the Filipino word ‘tapat’ and its various meanings as case study. Speaker: Remmon E. Barbaza is associate professor at the Department of Philosophy, Ateneo De Manila University. He holds a BA in Linguistics from the University of the Philippines in Diliman, an MA in Philosophy from the Ateneo de Manila University, and a PhD in Philosophy from the Hochschule für Philosophie in Munich, with a dissertation on Heidegger’s concept of dwelling, under the supervision of the late Prof. Dr. Gerd Haeffner, SJ. His research interests include Heidegger, language, translation, technology, environment, and the city.